Analysis of correlation factors and pregnancy outcomes of hypertensive disorders of pregnancy – a secondary analysis of a random sampling in Beijing, China. (19th March 2017) - Zhu, Yu-Chun; Yang, Hui-Xia; Wei, Yu-Mei; Zhu, Wei-Wei; Meng, Wen-Ying; Wang, Yong-Qing; Shang, Li-Xin; Cai, Zhen-Yu; Ji, Li-Ping; Wang, Yun-Feng; Sun, Ying; Liu, Jia-Xiu; et al.
Abstract: Objective : We aimed to assess the prevalence and risk factors for hypertensive disorders and to study the main pregnancy outcomes in the Beijing area of China. Study design : This study randomly sampled 15 hospitals in Beijing from Jun 2013 to Nov 2013 and evaluated 15 194 deliveries. Logistic regression analysis was used to study the association between risk factors and hypertensive disorders. Pregnancy outcomes included preterm birth, cesarean delivery and small for gestational age (SGA). Results : The prevalence of hypertensive disorders, preeclampsia (PE) and severe PE was 4.4, 2.7 and 1.8%, respectively. The risk factors for hypertensive disorders and severe PE were maternal body mass index before pregnancy, gestational weight gain (GWG), gestational diabetes and pre-gestational diabetes, and third trimester cholesterol (CHOL) levels. First trimester high-density lipoprotein was a protective factor for severe PE. The incidence of hypertensive disorders increased with maternal age. Preterm delivery, cesarean delivery and small infant size for gestational age were more prevalent in the severe PE group compared with the non-hypertensive group. Conclusions : In the Beijing area of China, maternal body mass index before pregnancy, GWG, maternal complications of gestational diabetes and pre-gestational diabetes, and third trimester CHOL levels are risk factors for both hypertensive disorders of pregnancy and severe PE. First trimester high-density lipoprotein is a protective factor for severe PE. Severe preeclampsia leads to a higher incidence of preterm delivery, cesarean delivery and SGA infants.